On the Approach to Calderón de la Barca's Dramatic Work in Secondary Education: From Curriculum to Textbook - Ulla Lorenzo, Alejandra (Didáctica. Lengua y Literatura, 2019)
The aim of the present article consists in proposing a critical approximation to the perspective from which the work of the dramatist Calderón de la Barca has been studied in the Secondary Education. For this will split of the indications that offers us the state curriculum, published in the Real Decreto 1105/2014 por el que se establece el currículo básico de la Educación Secundaria Obligatoria y del Bachillerato, through the contents of the subject Spanish Language and Literature. From this point we will examine a corpus of twenty-five textbooks of different Spanish publishers published between 2015 and 2016 with the purpose to analyse how focuses the process of education-learning of the work of this author in the first cycle of the ESO and in the first course of Bachillerato, the stage and course to which associates the didactic of the Spanish Golden Age literature.
Keywords: Calderón de la Barca; Secondary Education; curriculum; textbook